FORMULASI SUBSTRAT DASAR KOTORAN KAMBING DAN LIMBAH CAIR TEMPE DENGAN INOKULUM RUMEN SAPI UNTUK STUDI AWAL PRODUKSI BIOGAS - Dhini Arwindah; Umrah Umrah; Kasman Kasman (Biology Department, Mathematics and natural science, Tadulako University, 2018)
Production of biogas using the basic substrate of tempeh’s liquid waste and goat’s waste with the bacteria inoculum of cow’s rumen has been experimentally conducted. This study aims to produce biogas using the substrate with the bacteria inoculum of cow’s rumen and know the optimal mixture ratio of the basic substrate and the inoculum. In this study, the amounts of basic substrate applied were 500 g chicken’s waste and 500 mL liquid waste of tempeh. The study was designed using Complete Random Design comprising 6 treatments with 3 times repetitions, respectively. The treatments tested were P0 (100% basic substrate), P1 (80% basic substrate + 20% inoculum), P2 (60% basic substrate + 40% inoculum), P3 (40% basic substrate + 60% inoculum), P4 (20% basic substrate + 80% inoculum), P5 (100% inoculum). These treatments were fermented with anaerob bacteria for 10 days in the fermentor 1000 mL mounted with the biogas collecting balloon. Variables observed in this study were the measurements of biogas volume, culture medium pH, and biogas burning temperature, and the testing of biogas flame colour. Based on the observation result, three of the six examined treatments which could able to produce biogas were P2, P3 and P4 with the respective volume of 160 cm3, 143 cm3, and 118 cm3. While, the measured values of culture medium pH and biogas burning temperature were 6,87-7,10 and 152oC with the flame of red colour. This study shows that the optimal mixture ratio of the basic substrate and the inoculum for producing biogas is 3:2, and the produced biogas is potential to be used as an alternative energy.